2013
DOI: 10.2215/cjn.04980512
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Analysis of Nutritional Scores for Serial Monitoring of Nutritional Status in Hemodialysis Patients

Abstract: SummaryBackground and objectives This study aimed to compare the longitudinal performance of the malnutritioninflammation score (MIS) and the geriatric nutritional risk index (GNRI), two nutritional scores for patients on maintenance hemodialysis.Design, setting, participants, & measurements Nutritional scores, dietary intake, biochemical markers, and body composition analysis were performed at baseline and at 6, 12, and 18 months after enrollment (which took place from January through December 2006) on 75 pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 26 publications
3
56
0
6
Order By: Relevance
“…2 According to another recent study, GNRI is a valid tool for the longitudinal assessment of nutritional status in HD patients. 11 Our previous study also showed similar findings. 12 In the current study, at three months, total cholesterol and BUN, both of which are nutritional indicators, were higher in the group with a higher GNRI at three months.…”
Section: Discussionsupporting
confidence: 80%
“…2 According to another recent study, GNRI is a valid tool for the longitudinal assessment of nutritional status in HD patients. 11 Our previous study also showed similar findings. 12 In the current study, at three months, total cholesterol and BUN, both of which are nutritional indicators, were higher in the group with a higher GNRI at three months.…”
Section: Discussionsupporting
confidence: 80%
“…With regard to nutritional status, most of studies have shown that MHD associates with a significant decline in certain laboratory nutritional parameters, including albumin (26,27), as well as anthropometric measurements (27,28). GNRI, an objective and simple nutritional index, has also been reported to decrease significantly with time in patients on MHD in a recent prospective longitudinal study (29). The longitudinal behavior of SUA may be explained as follows: it is a proposed nutritional marker in the MHD population as reported in a recently published prospective observational study (15), and changes in SUA levels over time may simply follow changes in nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the overall nutritional status was assessed by GNRI, which may not be the ideal nutritional marker in the MHD population. Despite the observed significant associations of GNRI with dietary intake, laboratory markers of nutrition, body composition, and prognosis (29,44), the only validation study of GNRI as a nutritional marker in the MHD population was conducted in Japanese patients on HD (45). Fifth, the proportion of cardiovascular deaths may be underestimated, because the causes of death were extracted from patient records and were not confirmed by autopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline nutritional status was assessed in all participants at enrolment.Because MIS is the most validated nutritional method, it is used as the reference standard for the presence of PEW [13]. MIS was calculated from 7 categories of the modified SGA score together with the 3 additional components of body mass index (BMI), serum albumin, and serum total iron-binding capacity (TIBC) [3,14].…”
Section: Methodsmentioning
confidence: 99%
“…The sum of ten MIS categories ranges from 0 (normal) to 30 (severely malnourished). The cutoff value for MIS-positive status (malnutrition) was defined as 6 or more because patients with MIS ≥6 were associated with increased morbidity and mortality compared with patients who had MIS <6 in previous studies [4,13]. …”
Section: Methodsmentioning
confidence: 99%